Fitoremediasi Air Limbah Laundry Menggunakan Eceng Gondok (Eichhornia Crassipes) untuk Meningkatkan Kualitas Air - Listiatie Budi Utami; Telly Indi Cahyaning Puteri (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Laundry waste contains phosphates which cause eutrophication. This research aims to determine the effect of water hyacinth on wastewater quality and determine the best wet weight in reducing phosphate levels in laundry wastewater. The research was conducted at the Green House and Biological Research Laboratory of Ahmad Dahlan University, RAL research design with 4 treatments A (0 g plants); B (100g plant); C (200g plant); D (300g plants) with five times 5 repetitions. The results showed that variations in plant wet weight had an effect on improving the quality of laundry wastewater but did not differ significantly in temperature, TDS, DO and phosphate parameters. The length of plant roots increases in size.  The conclusion of this research is that varying the wet weight of water hyacinth has a significant effect on the parameters measured except pH, TDS and phosphate. Giving weight variations to laundry waste can affect the growth of water hyacinth roots. The best wet weight to improve water quality is 300 g of water hyacinth.